The Role of Compliance Function as a Moderation in the Relationship of Good Corporate Governance (GCG) and Enterprise Risk Management (ERM) against the Value of Listed State-Owned Enterprises in Indonesia - Yehezkiel Adiperwira (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Organizations are affected by the governance framework when conducting business activities. Organizations need to ensure economic, social and environmental added value. Changes in the business environment and technological developments cause every company to need to increase the value of the company. This ultimately led to a good supervision system called Good Corporate Governance (GCG). This research specifically raised SOEs as research objects because of SOEs.  This study aims to test and analyze the influence of Corporate Governance and Enterprise Risk Management (ERM), to test and analyze the impact of moderation compliance functions on the relationship between Corporate Governance, Compliance Function on the relationship between Enterprise Risk Management (ERM), towards the Value of Listed State-Owned Enterprises in Indonesia.  This is research with a quantitative approach. This study examines the influence of Good Corporate Governance (GCG) and the implementation of risk management on Company Value with the disclosure of Fraud Control Plan as moderation. The sample selection conducted in this study uses a non probability sampling method with a purposive sampling method.  In state-owned enterprises listed on the IDX, the implementation of Good Corporate Governance (GCG) has a significant positive effect on the value of the company. In state-owned enterprises listed on the IDX, ERM disclosure has a positive and significant effect on the value of the company. In state-owned enterprises listed on the IDX, the compliance function is not able to moderate the influence of GCG implementation on the value of the company. In state-owned enterprises listed on the IDX, the compliance function is not able to moderate the influence of ERM disclosure on the value of the company.